Biochemical and clinical features of hereditary hyperprolinemia. Issue 4 (August 2014) - Mitsubuchi, Hiroshi; Nakamura, Kimitoshi; Matsumoto, Shirou; Endo, Fumio
Abstract There are two classifications of hereditary hyperprolinemia: type I (HPI) and type II (HPII). Each type is caused by an autosomal recessive inborn error of the proline metabolic pathway. HPI is caused by an abnormality in the proline‐oxidizing enzyme (POX). HPII is caused by a deficiency of Δ‐1‐pyrroline‐5‐carboxylate (P5C) dehydrogenase (P5CDh). The clinical features of HPI are unclear. Nephropathy, uncontrolled seizures, mental retardation or schizophrenia have been reported in HPI, but a benign phenotype without neurological problems has also been reported. The clinical features of HPII are also unclear. In addition, the precise incidences of HPI and HPII are unknown. Only two cases of HPI and one case of HPII have been identified in Japan through a questionnaire survey and by a study of previous reports. This suggests that hyperprolinemia is a very rare disease in Japan, consistent with earlier reports in Western countries. The one case of HPII found in Japan was diagnosed in an individual with influenza‐associated encephalopathy. This suggests that HPII might reduce the threshold for convulsions, thereby increasing the sensitivity of individuals with influenza‐associated encephalopathy. The current study presents diagnostic criteria for HPI and HPII, based on plasma proline level, with or without measurements of urinary P5C. In the future, screening for HPI and HPII in healthy individuals, or patients with relatively common diseases such as developmental disabilities, epilepsy, schizophrenia or behavioral problems will be important.